Under the Mediterranean I : studies in maritime archaeology - Demesticha, Stella; Blue, Lucy Katherine; Baika, Kalliopi, 1974-; Beltrame, Carlo, 1969-; Blackman, D. J. (David J.); Cvikel, Deborah; Farr, Helen; Sivan, Dorit (Honor Frost Foundation Research Publication., 2021)
This volume is a collection of 19 articles in three sections reporting on recent research on the archaeology of shipwrecks, harbours, and maritime landscapes in the Mediterranean region. The shipwrecks section looks at excavated vessels from Mazotos, Modi Island, the port of Rhodes, Naples, and Narbonne, as well as a sailing reconstruction of the Ma'agan Mikhael ship.The harbours section includes articles on areas from the Levant to Seville looking at a variet.